Strategic dimensions of sustainability and resilience in the supply chain of the Aptiv Company - Inzunza Mejía, Patricia Carmina (2024)
This research analyzes the strategic dimensions of the Aptiv company's supply chain, as a model of optimal functioning in inventory management and supply flows that make it resilient and sustainable. The study has a qualitative approach, exploratory and descriptive, under a non-experimental design. The analytical method was developed for the review of scientific literature and the case study, following the principles of just-in-time and inventory management. The intervention model in professional practice, semi-structured interview techniques and the self-administered questionnaire were implemented. In conclusion, the social, environmental, quality industry and technological dimensions consolidate the supply chain, making it resilient and sustainable, through the application of strategies that optimize inventory management based on technology, experience and reinforced learning of the supply processes that allow a simple, friendly and resilient distribution, with environmental care and protection actions, as well as ethical and social responsibility strategies that strengthen governance and the relationship with its associated customers (Tier 2, Tier 3 and OEM); which is why the company not only permanently improves its sustainability strategy, but also provides continuity and monitoring of the guidelines of the Global Reporting Initiative (GRI) to maintain the application of quality standards; therefore, from a governance perspective, they undergo external evaluation processes to make their economic, technological, social and environmental impact visible.